2019
DOI: 10.1038/s41467-019-13246-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlled nonlinear magnetic damping in spin-Hall nano-devices

Abstract: Large-amplitude magnetization dynamics is substantially more complex compared to the low-amplitude linear regime, due to the inevitable emergence of nonlinearities. One of the fundamental nonlinear phenomena is the nonlinear damping enhancement, which imposes strict limitations on the operation and efficiency of magnetic nanodevices. In particular, nonlinear damping prevents excitation of coherent magnetization auto-oscillations driven by the injection of spin current into spatially extended magnetic regions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…In the last decade, nonlinear dissipation has attracted much attention with applications that span nanomechanics 1 , materials science 2 , biomechanics 3 , thermodynamics 4 , spintronics, 5 and quantum information 6 . It has been shown that the nonlinear dissipation process follows the empirical force model where τ nl1 is the nonlinear damping coefficient, x is the displacement, and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, nonlinear dissipation has attracted much attention with applications that span nanomechanics 1 , materials science 2 , biomechanics 3 , thermodynamics 4 , spintronics, 5 and quantum information 6 . It has been shown that the nonlinear dissipation process follows the empirical force model where τ nl1 is the nonlinear damping coefficient, x is the displacement, and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits significant strain-induced perpendicular magnetic anisotropy (PMA) with the effective anisotropy field µ 0 H a = 167 mT, which is very close to the saturation magnetization of the film µ 0 M s = 175 mT. This leads to the compensation of the effects associated with the dipolar anisotropy and thus results in the minimization of nonlinear magnon interactions 39 . The spin system of the BiYIG film is driven out of the equilibrium by spin torque through the injection of the pure spin current I s created by the SHE in the Pt electrode carrying dc electric current I .…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, in nanometer-thick YIG films, which can be efficiently driven by spin currents, the energy of the lowest magnon level contains a significant dynamic dipolar contribution, which results in a strong attractive interaction between magnons leading to spatial instabilities and collapses 27 , 38 . The nonlinearities associated with dipolar effects have also been recently shown to be responsible for the strong scattering of magnons out from the lowest-energy state preventing its overpopulation 39 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, Object-Oriented Micromagnetic Framework (OOMMF) simulations were performed on the filter structure shown in Figure 1a. OOMMF solves Landau-Lifshitz-Gilbert (LLG) equation using finite-difference methods [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%